Routine or selective carotid artery shunting for carotid endarterectomy (and different methods of monitoring in selective shunting) - Wilaiwan Chongruksut (2018)
BACKGROUND: Temporary interruption of cerebral blood flow during carotid endarterectomy can be avoided by using a shunt across the clamped section of the carotid artery. This may improve outcome. This is an update of a Cochrane review originally published in 1996 and previously updated in 2009. OBJECTIVES: To assess the effect of routine versus selective or no shunting during carotid endarterectomy, and to assess the best method for selecting people for shunting. SEARCH METHODS: We searched the Cochrane Stroke Group Trials Register (last searched August 2013), the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library, 2013, Issue 8), MEDLINE (1966 to August 2013), EMBASE (1980 to August 2013) and Index to Scientific and Technical Proceedings (1980 to August 2013). We handsearched journals and conference proceedings, checked reference lists, and contacted experts in the field. SELECTION CRITERIA: Randomised and quasi-randomised trials of routine shunting compared with no shunting or selective shunting, and trials that compared different shunting policies in people undergoing carotid endarterectomy. DATA COLLECTION AND ANALYSIS: Three review authors independently performed the searches and applied the inclusion criteria. For this update, we identified two new relevant randomised controlled trials. MAIN RESULTS: We included six trials involving 1270 participants in the review: three trials involving 686 participants compared routine shunting with no shunting, one trial involving 200 participants compared routine shunting with selective shunting, one trial involving 253 participants compared selective shunting with and without near-infrared refractory spectroscopy monitoring, and the other trial involving 131 participants compared shunting with a combination of electroencephalographic and carotid pressure measurement with shunting by carotid pressure measurement alone. In general, reporting of methodology in the included studies was poor. For most studies, the blinding of outcome assessors and the report of prespecified outcomes were unclear. For routine versus no shunting, there was no significant difference in the rate of all stroke, ipsilateral stroke or death up to 30 days after surgery, although data were limited. No significant difference was found between the groups in terms of postoperative neurological deficit between selective shunting with and without near-infrared refractory spectroscopy monitoring, However, this analysis was inadequately powered to reliably detect the effect. There was no significant difference between the risk of ipsilateral stroke in participants selected for shunting with the combination of electroencephalographic and carotid pressure assessment compared with pressure assessment alone, although again the data were limited. AUTHORS' CONCLUSIONS: This review concluded that the data available were too limited to either support or refute the use of routine or selective shunting in carotid endarterectomy. Large scale randomised trials of routine shunting versus selective shunting are required. No method of monitoring in selective shunting has been shown to produce better outcomes.